2022
DOI: 10.3389/fped.2022.842470
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety in Chinese Patients With Cleft Lip and/or Palate: A Preliminary Study

Abstract: ObjectivesTo preliminarily analyze factors that affected the prevalence of anxiety in Chinese patients with cleft lip and/or palate (CL/P).MethodsThe Generalized Anxiety Disorder Scale (GAD-7) was used to screen anxiety in Chinese CL/P patients. Non-CL/P individuals were also included as the control group. Sociodemographic and clinical data consisting of diagnosis, gender, only child or not, monthly household income, and current family location were collected to analyze possible factors that could affect the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…Our results showed that 6.5% of adolescent patients with CP were in moderate or severe anxiety, compared with 1.6% in the control group. However, no significant difference in total GAD-7 scores and scores of each item between the study group and the control group was found, which was consistent with the results of previous studies that there was no significant difference in life satisfaction and anxiety between patients with CP and the non-CP control group (17,33), but the proportion of patients with CP reporting anxiety problems was higher than that of the control group (34).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our results showed that 6.5% of adolescent patients with CP were in moderate or severe anxiety, compared with 1.6% in the control group. However, no significant difference in total GAD-7 scores and scores of each item between the study group and the control group was found, which was consistent with the results of previous studies that there was no significant difference in life satisfaction and anxiety between patients with CP and the non-CP control group (17,33), but the proportion of patients with CP reporting anxiety problems was higher than that of the control group (34).…”
Section: Discussionsupporting
confidence: 90%
“…The Generalized Anxiety Disorder 7-item (GAD-7) scale was given to adolescents themselves to assess their anxiety status over the last 2 weeks with 7 items graded on a 4-point Likert scale as 0 (not at all), 1 (several days), 2 (more than half the days), and 3 (nearly every day). The subjects were divided into normal (0-4), mild (5-9), moderate (10)(11)(12)(13)(14) and severe (15)(16)(17)(18)(19)(20)(21) according to the total score. Chinese-version GAD-7 has been widely used in Chinese population, notably in the cleft field (17), and has shown good reliability and validity among Chinese adolescents aged 10-17 years old (12).…”
Section: Assessment Of Anxietymentioning
confidence: 99%
See 1 more Smart Citation
“…Patients visiting West China Hospital of stomatology, Sichuan University, from July 2019 to October 2020, were enrolled. To the patients with CL/P, demographic and clinical data were collected, including diagnosis (CL, cleft lip only; CP, cleft palate only; CLP, cleft lip and palate), gender, age, only child or not, region (urban or rural), and monthly family income (CNY less than 500; 500–1000; 3000–5000; 5000–10,000; 10,000–50,000; more than 50,000) [ 15 ].…”
Section: Methodsmentioning
confidence: 99%
“…The primary purpose of the ONF obturator is to obstruct abnormal communication between the oral and nasal cavities. However, in patients with cleft palate, velopharyngeal insufficiency (VPI) can also be the cause of speech problems and affect their quality of life [ 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ]. Both ONF and VPI can contribute to the speech dysfunction of the patient [ 49 , 50 , 51 ], so both aspects should be considered during the manufacture of the obturator.…”
Section: Development Of Onf Obturatormentioning
confidence: 99%